2009
DOI: 10.1002/jor.20884
|View full text |Cite
|
Sign up to set email alerts
|

Hip resurfacing increases bone strains associated with short‐term femoral neck fracture

Abstract: Short-term femoral neck fracture is a primary complication associated with contemporary hip resurfacing. Some fractures are associated with neck notching, while others occur in the absence of notching. These unexplained fractures may be due to large magnitude strains near the implant rim, which could cause bone damage accumulation and eventual neck fracture. We used statistically augmented finite element analysis to identify design and environmental variables that increase bone strains near the implant rim aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…The main strain alterations observed were strain shielding in the femoral head, particularly in the superior zones, and increased strain in the femoral neck, again most notable superiorly. These patterns of load transfer change have been reported in previous FE and experimental work (Huiskes et al, 1985;Watanabe et al, 2000;Ong et al, 2006;Taylor, 2006;Cristofolini et al, 2009;Long et al, 2009).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The main strain alterations observed were strain shielding in the femoral head, particularly in the superior zones, and increased strain in the femoral neck, again most notable superiorly. These patterns of load transfer change have been reported in previous FE and experimental work (Huiskes et al, 1985;Watanabe et al, 2000;Ong et al, 2006;Taylor, 2006;Cristofolini et al, 2009;Long et al, 2009).…”
Section: Discussionsupporting
confidence: 64%
“…Previous FE and experimental work have shown increased strain in the superior femoral neck although not over a volume sufficient to cause fracture but the addition of a notch could be enough to change this (Watanabe et al, 2000;Ong et al, 2006;Taylor, 2006;Cristofolini et al, 2009). Although Long et al (Long et al, 2009) argued that short term neck fracture is not always accompanied by evidence of notching, they suggested that bones with lower modulus and where higher loads were applied, the areas around the implant rim would experience high strain concentrations and may suffer damage accumulation, leading to fatigue failure before the bone adaption cycle can complete in response. The average strain changes predicted in the neck in this study are of a similar magnitude to earlier predictions, supporting this possibility.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In other cohorts, femoral neck fracture has had an incidence of approximately 1-3% [19,35,36], and in several cases could be explained by surgical technique. Ritter et al [21] reported an 18% femoral neck fracture rate, but [7,13,17,22,31,[37][38][39][40][41][42][43][44][45][46]. The results of this study suggested that the femoral head resorption was caused largely by stress shielding from the thick metal shell of the prosthesis head, and was only slightly improved in the immediate postoperative situation by the stem design.…”
Section: Discussionmentioning
confidence: 70%
“…A number of studies using finite element (FE) analysis have reported the generation of elevated strains in the proximal femoral neck-component junction and strain shielding in the resurfaced femoral head, indicating the risk of neck fracture and adverse bone remodelling (Gupta et al, 2006;Long et al, 2009;Pal et al, 2009;Watanabe et al, 2000). The causes of failure seem to depend on several biomechanical factors related to the implant (design, positioning, orientation, fixation method) and the patient (bone quality, joint loading).…”
Section: Introductionmentioning
confidence: 96%